Analysis of Knowledge and Beliefs of Women With and Without HPV Diagnosis About the Virus and Vaccine - Tandogan, Ozden; Ak, Eda Yakit; Sen, Mehmet Ali; Akdemir, Arzu; Sabancilar, Gulin Gulen; Yarasir, Ezgi (Wiley, 2025)
Purpose: This study aimed to compare the knowledge and health beliefs of women with and without an HPV diagnosis regarding the virus and its vaccine. Methods: Designed as a cross-sectional case-control study, the research was conducted with 478 women attending a gynecology outpatient clinic in Istanbul. Data were collected using a sociodemographic questionnaire, the Human Papillomavirus Knowledge Scale (HPV-KS), and the Health Belief Model Scale for HPV Infection and Vaccination (HPV-HBMS). Results: The findings indicated that women diagnosed with HPV had significantly higher knowledge scores and a greater perceived seriousness of the infection compared to those without an HPV diagnosis (p < 0.05), although overall knowledge levels remained low in both groups. A significant difference was also found between the two groups in terms of HPV vaccine awareness, Pap smear testing, and vaccination status. Logistic regression analysis revealed that higher education level, older age, a family history of cervical cancer, previous HPV vaccination, and having undergone Pap smear testing were associated with a reduced risk of HPV infection (p < 0.05). Conclusion: These findings underline the importance of targeted education and outreach efforts to improve HPV awareness and vaccine uptake among women.
Keywords: health belief model; HPV; vaccine; vaccine hesitancy; women